O011 Effect of Continuous Positive Airway Pressure on Quality of Life and Treatment Burden in Children with Obstructive Sleep Apnoea. (9th November 2022) - Nisbet, L; Ellis, K; Mihai, R; Davey, M; Nixon, G
Abstract: Introduction: Increasing numbers of children with obstructive sleep apnoea (OSA) require treatment with continuous positive airway pressure (CPAP). We aimed to assess the impact on quality of life (QOL) and treatment burden for caregivers of children requiring CPAP. Methods: Prospective study of children commencing outpatient CPAP in a tertiary sleep unit 2020-2022. Questionnaires regarding sleep-related symptoms (PROMIS Pediatric Sleep Disturbance and Sleep-Related Impairment), QOL (OSA-18, QI-Disability), caregiver burden (Caregiver Strain Questionnaire) and overall health impact (Glasgow Children's Benefit Inventory) were completed by caregivers at commencement of CPAP and 6 weeks later. Progress: Complete data available to date in 24 children (6F; median age 12.5y, range 6-18y; median OAHI 9.2/hr; median BMI 30.7). OSA-related QOL significantly improved at follow-up (OSA-18 total and domain scores all p<0.001). There were significant improvements in child general QOL (p<0.0001), sleep disturbance (p<0.01) and sleep-related impairment (p<0.001). Caregivers rated CPAP as beneficial to their child's general condition (mean 30, where maximum harm -100, maximum benefit +100). Caregiver strain reduced at follow-up (p<0.001) and benefit outweighed inconvenience (p<0.0001). 3 caregivers scored inconvenience higher than benefit; 1 scored them equally. 1 caregiver rated CPAP harmful and 3 caregivers reported no effect on their child's general health. Outcome: CPAP results in significant improvements in QOL and sleep-related symptoms in children with OSA, and reductions in caregiver strain. Perceived benefits generally outweighed the burden of treatment, but not for all families. Further analysis will investigate how the balance of benefit to burden relates to adherence and the effect of co-morbidities.